HCI beyond the GUI design for haptic, speech, olfactory and other nontraditional interfaces - Kortum, Philip (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2008)
As technology expands and evolves, one-dimensional, graphical user interface (GUI) design becomes increasingly limiting and simplistic. Designers must meet the challenge of developing new and creative interfaces that adapt to meet human needs and technological trends. HCI Beyond the GUI provides designers with this know how by exploring new ways to reach users that involve all of the human senses. Dr. Kortum gathers contributions from leading human factors designers to present a single reference for professionals, researchers, and students. . Explores the human factors involved in the design and implementation of the nontraditional interfaces, detailing design strategies, testing methodologies, and implementation techniques . Provides an invaluable resource for practitioners who design interfaces for children, gamers and users with accessibility needs . Offers extensive case studies, examples and design guidelines.
1. Introduction to the Human Factors of Nontraditional Interfaces -- Philip Kortum -- 2. Haptic Interfaces -- Marcia K. O'Malley, Abhishek Gupta -- 3. Gesture Interfaces -- Michael Nielsen, Thomas B. Moeslund, Moritz Storring, and Erik Granum -- 4. Locomotion Interfaces -- Mary C. Whitton, Sharif Razzaque -- 5. Auditory Interfaces -- S. Camille Peres, Virginia Best, Derek Brock, Christopher Frauenberger, Thomas Hermann, John G. Neuhoff, Louise Valgeπrur Nickerson, Barbara Shinn-Cunningham, Tony Stockman -- 6. Designing Usable Voice User Interfaces -- Susan L. Hura -- 7. Interactive Voice Response Interfaces -- Jeff Brandt -- 8. Olfactory Interfaces -- Yasuyuki Yanagida -- 9. Taste Interfaces -- Hiroo Iwata -- 10. Small-Screen Interfaces -- Daniel W. Mauney, Chris Masterton -- 11. Multimode Interfaces: Two or More Interfaces to Accomplish the Same Task -- Aaron W. Bangor, James T. Miller -- 12. Multimodal Interfaces: Combining Interfaces to Accomplish a Single Task -- Paulo Barthelmess, Sharon Oviatt.
Includes bibliographical references and index.
Keywords: Human-computer interaction; Graphical user interfaces (Computer systems); Electronic books